Discomfort of pregnant women on the quality sleep of third trimester pregnant women - Desmarnita, Ulty; Fadilasari, Yasinta; Mulyanti, Yuli (Asian Journal of Pharmaceutical Research and Development, 2023)
Background: Physical changes in the third trimester of pregnancy will appear due to physiological changes and psychological changes that cause discomfort. This uncomfortable condition causes sleep disturbances in the mother. Objective: To determine the relationship between discomfort in pregnancy and the quality of sleep of third trimester pregnant women at the Makasar Health Center. Method: This was a descriptive analytic study and a cross sectional study design. Determination of the number of samples using the sample size application resulted in 40 samples of pregnant women in the third trimester. The sampling technique used purposive sampling. When the study was conducted in September-November 2020. The research instrument used the Pittsburgh Sleep Quality (PSQI) questionnaire with cronbach alpha 0.83 and the cronbach alpha 0.86 physical discomfort disorder questionnaire was tested for validity with r-count> 0.367. Data were processed by crosstab and analyzed by Chi-square. Results: Most of the respondents experienced discomfort (66.7%) and experienced poor sleep quality (70.0%). The association between pregnancy discomfort and sleep quality of third trimester pregnant women with a p value of 0.030. Conclusion: There is a relationship between discomfort in pregnancy and the quality of sleep in the third trimester of pregnant women. Recommendation: From this research, it is hoped that it can be used as input for health workers, especially nursing, to provide education on how to reduce pregnancy discomfort and good sleep quality in third trimester pregnant women.